2023
DOI: 10.3389/fphar.2023.1053680
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of the endocannabinoid system on glial cells toward cognitive function in Alzheimer’s disease: A systematic review and meta-analysis of animal studies

Abstract: Objective: Over the last decade, researchers have sought to develop novel medications against dementia. One potential agent under investigation is cannabinoids. This review systematically appraised and meta-analyzed published pre-clinical research on the mechanism of endocannabinoid system modulation in glial cells and their effects on cognitive function in animal models of Alzheimer’s disease (AD).Methods: A systematic review complying with PRISMA guidelines was conducted. Six databases were searched: EBSCOHo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 153 publications
0
2
0
Order By: Relevance
“…This interaction is especially significant, particularly in the early stages of the disease, such as during the upregulation of CB2 receptor expression involved in the development of neuroinflammation [ 34 ]. However, targeting the ECS is not without its challenges, as CB1 and CB2 receptors serve as essential regulators of neuronal function, exerting varied effects on neuronal responses [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This interaction is especially significant, particularly in the early stages of the disease, such as during the upregulation of CB2 receptor expression involved in the development of neuroinflammation [ 34 ]. However, targeting the ECS is not without its challenges, as CB1 and CB2 receptors serve as essential regulators of neuronal function, exerting varied effects on neuronal responses [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the great potential of ECS to control degenerative diseases such as AD, due to its anti-inflammatory and neuroprotective properties that involve astrocyte engagements. Interestingly, cannabinoid signaling in glial cells essential has this function, since neuroimmunomodulation of glial cells by exogenous cannabinoid treatment enhances behavioral and cognitive responses, resulting in improved learning and memory-related symptoms in AD (for review see [ 29 ]).…”
Section: Introductionmentioning
confidence: 99%